A preliminary study on knowledge retention strategy in Faculty of Information Management of UiTM / Abdurrahman Jalil ... [et al.] - Jalil, Abdurrahman; Abdul Ghani, Muhammad Arif; Wahab, Hairani; Mustafa, A'dillah; Shibghatullah, Abdul Samad (Faculty of Information Management, 2023)
Knowledge retention strategy is very important to retain valuable knowledge in an organization. Like other organizations, Faculty of Information Management in UiTM Puncak Perdana campus is facing an issue of lack of staff due to retirement and resignation of experts. This study therefore is conducted to provide preliminary insight on the knowledge retention strategy implemented in the faculty. This study adopts one-on-one interview approach where three participants who are selected based on their roles in the faculty have been interviewed to identify and understand the practices of the strategies. The findings show that there are some initiatives have been adopted by the faculty to retain valuable knowledge for the staff. Thus, it could be a reference for the faculty to enhance the knowledge retention strategies in future in order to have better impact.